2022
DOI: 10.3390/ijms232314883
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Resolvins in Chronic Inflammatory Response

Abstract: An inflammatory response is beneficial to the organism, while an excessive uncontrolled inflammatory response can lead to the nonspecific killing of tissue cells. Therefore, promoting the resolution of inflammation is an important mechanism for protecting an organism suffering from chronic inflammatory diseases. Resolvins are a series of endogenous lipid mediums and have the functions of inhibiting a leukocyte infiltration, increasing macrophagocyte phagocytosis, regulating cytokines, and alleviating inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 138 publications
(155 reference statements)
0
13
0
Order By: Relevance
“…59 It has been suggested that resolvins such as RvD1 and RvE1 play a vital role in the pathology of certain joint inflammation, neuroinflammation, vascular inflammation and tissue inflammation. 60 Lower levels of resolvins observed in the present study suggests that a reduction in pro-resolving mediators in the placentae of women with GDM may lead to inflammation.…”
Section: Discussionmentioning
confidence: 44%
“…59 It has been suggested that resolvins such as RvD1 and RvE1 play a vital role in the pathology of certain joint inflammation, neuroinflammation, vascular inflammation and tissue inflammation. 60 Lower levels of resolvins observed in the present study suggests that a reduction in pro-resolving mediators in the placentae of women with GDM may lead to inflammation.…”
Section: Discussionmentioning
confidence: 44%
“…Furthermore, we observed significantly enhancements in “fatty acid metabolism,” and “linoleic acid metabolism” in lung microbiome with lung cancer, and they showed inverse correlation between the lung and gut microbiomes. Linoleic acid is a source of DHA, EPA, and arachidonic acids [ 48 , 49 ]. Therefore, we speculated that these alterations in metabolic functions in the lung and gut microbiomes could affect the progression of lung cancer through the upregulation of lipid metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, LTB4 and prostaglandin E2, which aggravate lung cancer [ 25 , 27 ], are upregulated in the lungs. However, isohumulone, which is a PPARγ activator [ 28 ], and resolvin (an ω-3 PUFA and SPM) [ 48 ], which has anti-inflammatory effects, were upregulated in the small intestine and colon, respectively [ 18 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both series promote neutrophil digesting and macrophage apoptosis. [19][20][21] Resolvin E1 (RvE1), derived from the omega-3 polyunsaturated fatty acids, eicosapentaenoic acid (EPA), has been demonstrated to successfully treat periodontitis in animal models. 22 Furthermore, it has been reported that RvE1 affects bone remodelling by modulating the osteoclast differentiation, rescuing OPG production and consequently, reducing the RANKL/OPG ratio.…”
Section: Introductionmentioning
confidence: 99%
“…While the D‐series controls inflammation in brain tissues, the E‐series inhibits neutrophil trans‐endothelial migration. Both series promote neutrophil digesting and macrophage apoptosis 19–21 …”
Section: Introductionmentioning
confidence: 99%